2015
DOI: 10.1039/c5cc03398e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanocrystals of Zr-based metal–organic frameworks with csq-net: significant enhancement in the degradation of a nerve agent simulant

Abstract: The synthesis of nano-sized particles of NU-1000 (length from 75 nm to 1200 nm) and PCN-222/MOF-545 (length from 350 nm to 900 nm) is reported. The catalytic hydrolysis of methyl paraoxon was investigated as a function of NU-1000 crystallite size and a significant enhancement in the rate was observed for the nano-sized crystals compared to microcrystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
179
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 212 publications
(191 citation statements)
references
References 61 publications
4
179
0
8
Order By: Relevance
“…MOFs have been employed as catalysts and catalyst supports, in part because of their ordered nature, structural tunability, and permanent porosity . We and others have shown that fine‐tuning pore size, particle size, metal node connectivity and chemical composition can favorably affect the activity of MOF‐based catalysts in the hydrolysis of a nerve agent simulant, dimethyl 4‐nitrophenyl phosphate (DMNP). Importantly, DMNP has been shown to be effective for mimicking the reactivity of organophosphonate‐based nerve agents (Scheme ) .…”
Section: Figurementioning
confidence: 99%
“…MOFs have been employed as catalysts and catalyst supports, in part because of their ordered nature, structural tunability, and permanent porosity . We and others have shown that fine‐tuning pore size, particle size, metal node connectivity and chemical composition can favorably affect the activity of MOF‐based catalysts in the hydrolysis of a nerve agent simulant, dimethyl 4‐nitrophenyl phosphate (DMNP). Importantly, DMNP has been shown to be effective for mimicking the reactivity of organophosphonate‐based nerve agents (Scheme ) .…”
Section: Figurementioning
confidence: 99%
“…In order to synthesize the MOF-525 crystals with various sizes, the additive amount of modulator (i.e., benzoic acid) during the synthetic process was changed to be 2.7 g, 2.0 g, 1.35 g, 1.1 g, and 0.9 g, respectively; similar strategies have been used to control the crystal size of other MOFs in literature. [42][43][44] The suspensions of MOF-525 crystals in DMF with a concentration of 20 mg/mL were prepared by the same protocol reported in details in the previous study. 41 For material characterizations, the dried powders of MOF-525 crystals were collected by the activation process reported previously.…”
Section: Preparation Of the Inks And Powders Of Mof-525 Crystalsmentioning
confidence: 99%
“…To synthesize zirconium-based porphyrinic MOF crystals with smaller sizes, benzoic acid, a well-known nucleation modulator for MOF synthesis, [42][43][44] was used at various concentrations in the solvothermal synthesis. The scanning electron microscopy (SEM) images of the synthesized MOF powders are shown in Fig.…”
Section: Ink Formulationmentioning
confidence: 99%
“…[6] Metal-organic frameworks (MOFs) are self-assembled, and atomically precise porous materials comprising metal ions/clusters and organic linkers. [8] We and others have shown that fine-tuning pore size, [9] particle size, [10] metal node connectivity [11] and chemical composition [12] can favorably affect the activity of MOF-based catalysts in the hydrolysis of anerve agent simulant, dimethyl 4-nitrophenyl phosphate (DMNP). [8] We and others have shown that fine-tuning pore size, [9] particle size, [10] metal node connectivity [11] and chemical composition [12] can favorably affect the activity of MOF-based catalysts in the hydrolysis of anerve agent simulant, dimethyl 4-nitrophenyl phosphate (DMNP).…”
mentioning
confidence: 99%